Adolescence : The Survival Guide for Parents and Teenagers - Fenwick, Elizabeth and Smith, Tony (London Dorling Kindersley, 1993)
Written for teenagers and their parents in alternating sections. This guide offers solutions and problem-solving scenarios for young people and their concerns.
Include Illustration and Index
Keywords: Adolescence -- Parent and teenager -- Teenagers--Family relationships